Two new species of Exetastes (Hymenoptera: Ichneumonidae: Banchinae) from the Peruvian Andes - Reshchikov, Alexey; Alvarado, Mabel (European Journal of Taxonomy, 2022)
Two new species of Exetastes Gravenhorst, 1829 from the Peruvian Andes are described and illustrated: E. andensis sp. nov. and E. tullu sp. nov. Presently, 38 species of Exetastes have been recorded in the Neotropical region. Our discoveries are the first records of the genus in Peru and the Andean region.